Os bens aprendidos e sequestrados em procedimentos penais e o financiamento de atividades educacionais nos presídios - Saadi, Ricardo Andrade (2012)
The present study comprises two issues related to the Brazilian scenario: the absence of educational activities in prisons and the new strategy of Brazilian authorities in fighting against organized crime, which in based on the impoverishment of criminal activity, creating a buildup situation in police and judicial deposits of goods constricted in criminal proceedings. The main goal of this work is demonstrating that educational activities in prisons can be financed by the amounts obtained by selling the above mentioned assets.